Emerging themes in necrotising otitis externa: a scoping review of the literature from 2011 to 2020 and recommendations for future research. Issue 7 (20th July 2022) - Stapleton, E; Watson, G
Abstract: Objective: Necrotising otitis externa is an invasive, infective condition, with minimal evidence underpinning its diagnosis and management. This work aimed to analyse literature from the past decade, to identify emerging themes and important topics for future research. Methods: A robust literature search and review were conducted by two researchers. Sixty studies were filtered into the final review. A grounded theory approach was used to identify core themes. Data within these themes formed the basis of the review. Results: There is no consensus regarding a clinical definition or outcome measures of necrotising otitis externa, and there exists no level 1, 2 or 3 evidence to diagnose, investigate, monitor or treat necrotising otitis externa. Emerging themes in the literature direct researchers to important topics for future clinical trials, including risk factors, microbiological culture, management strategies and radiology. Conclusion: In order to optimise understanding and management of necrotising otitis externa, future research requires robust clinical trials and consistently reported outcome measures.